Identificación y análisis de factores de éxito de la gerencia de proyectos en algunas PyMEs del sector TI en Bogotá D.C. Colombia. (2016)
This research presents the identification and analysis of the success factors in the project management of information technology (IT) in small and medium enterprises (SME) located in Bogotá, Colombia. Based on literature review combined with the perception of success by top managers, project leaders and project managers through interviews, focus group and questionnaires, a list of potential success factors of IT project management were identified; subsequently, an analysis were conducted to consolidate a final set of eleven (11) success factors. The findings of our study reveal that aspects related to scope, planning, control, communication, stakeholders, project team, project manager, organizational characteristics and top management support are the most important to the successful project management in some IT small and medium enterprises.